(untitled) (American Journal of Islam and Society, 1993)
The news of Professor Mahmoud Abu Saud’s death has saddened us all. For several decades, he has been a prominent figure in the seminars and conferences of the Association of Muslim Social Scientists (AMSS), the International Institute of Islamic Thought (IIIT), the Islamic Society of North America (ISNA), the American Muslim Council (AMC), and other Islamic and interfaith organizations. His passionate commitment to the reconstruction of Islamic thought, as well as his tireless involvement in writing, lecturing, and touring from country to country and from city to city, were a great inspiration to our young scholars. As a learned scholar, Social scientist, and, in particular, an economist, friend, and mentor, he will be missed in many forums. He served as a referee for the American Journal of Islamic Social Sciences (AJISS), and his comments were always objective and straightforward. His ideas, ideals, and intellectual and moral heritage will continue to inspire his friends and students. We pray that Almighty Allah will cover him with His mercy and also grant us patience and help us to emulate some of his extra- The growth and development of MISS was one of the aspitations of the late Mahmoud Abu Saud. Our constant struggle to enhance the intellectual content of the journal will be a source of reward to the departed soul of that great mujdhid. For verily “we belong to Allah and to Him we return.“ This issue begins with Mahmoud Dhaouadi’s paper on Islamic knowledge and the rise of the new science. In the last few decades, Mahmoud Dhaouadi argues, western science has begun to shift from what is called classical science to new science. This vision of the emerging new science promises to heal the division between matter and spirit and to do away with the mechanical dimension of the world. However, the process of reconciliation between religion and science in modem western culture still faces a great many hurdles. Islam, on the other hand, looks at knowledge and science as a continuum whereby divine and human knowledge and science both cooperate with and complement each other. He gives examples from the practices of classical Muslim scholars, such as Ibn Khaldin, who based their research on this approach. Knowledge ...